A New Augmented Lagrangian Method for Equality Constrained Optimization with Simple Unconstrained Subproblem - Hao Zhang; Qin Ni (Discrete Dynamics in Nature and Society)
We propose a new method for equality constrained optimization based on augmented Lagrangian method. We construct an unconstrained subproblem by adding an adaptive quadratic term to the quadratic model of augmented Lagrangian function. In each iteration, we solve this unconstrained subproblem to obtain the trial step. The main feature of this work is that the subproblem can be more easily solved. Numerical results show that this method is effective.